Pemetaan Pemborosan (Waste) Dalam Proses Produksi Pada Seksi Painting Plastic (Studi Kasus Perusahaan Otomotif) - Chrinadio Chrisna; Ahmad Ahmad (Jurusan Teknik Industri, Fakultas Teknologi Indusri Universitas Trisakti, 2018)
The painting process is one of the very important processes in the automotive motorcycle industry. One of the problems in the painting process is the occurrence of waste in the use of paint materials or ussualy referred as overquota, which is caused by the presence of waste in the painting process. The VSM (Value Stream Mapping) method was used to reduce the waste that occurs, identifying waste begins using the Waste Assessment model (WAM) to determine the percentage of waste. The identified wastes are 3 types of waste with the greatest weight, namely defect (30.1%), motion (16.1%), and waiting (13.1%). Next is the selection of detailed mapping tools using VALSAT (Value Stream Analysis Tools). The tools chosen are 2 tools with the greatest value. Analysis of waste defect using Pareto diagram shows the most dominant rejects are dirty, saggy, and thin, so further analysis is focused on the three rejects using p chart, fishbone diagram, and FMEA (Failure Method Effect Analysis) . The proposals given to reduce waste are replacing SOPs, repairing work station, and making checksheets and material collection forms. After the proposal is applied, it is found that PCE increases by 17% and the reduction in Manufacturing Lead Time value by 26.15%